Magmatic and Metamorphic Fluids in Pegmatite Development: Evidence from Borujerd Complex, Iran (Journal of Sciences, Islamic Republic of Iran)
The Borujerd complex of western Iran is composed of intrusions and their surrounding contact aureole, with, pegmatites and quartz veins. Pegmatites differ in mineralogy, origin and age, and two groups can be distinguished. The Older Pegmatites (about 120 Ma age) intruded contact metamorphic rocks from the early magmatic stage, while the Younger pegmatites (52-70 Ma age) formed during the late magmatic stage. Fluid inclusions from quartz veins, pegmatites and hornfelses have been studied using microthermometry, scanning electron microscopy, laser Raman spectroscopy and crush leach analysis to evaluate the source of fluids from which pegmatites formed. Host minerals of fluid inclusions in pegmatites are quartz and tourmaline, whereas in the hornfelses they are andalusite and quartz. Low salinity H2O inclusions are common in the Older Pegmatites and quartz veins whereas high salinity H2O inclusions occur in Younger Pegmatites. CO2-H2O fluid inclusions occur in Older Pegmatites and hornfelses, and in addition pure CO2 inclusions are observed in some hornfelses. The distribution of the different types of fluid inclusions suggests that CO2 fluids evaluated during metamorphism. The source of the carbon may be graphite which is present in hornfelses and the basement mica schists. Low salinity fluids in Older Pegmatites, quartz veins and hornfelses could have formed from low salinity late magmatic fluids. However, some mixing took place between magmatic fluids and metamorphic fluids to form CO2-H2O inclusions. High salinity magmatic fluids are only associated with Younger pegmatites and show low first ice melting temperature (?61.0 to ?75.5°C), probably due to the presence of Ca.